Analysis of Legality and Sharia Compliance of the Kitabisa.com Crowdfunding Platform in Digital Islamic Philanthropy in Indonesia - Raha Bahari; Aliyyah Azzah Sabina; Aryo Salasa (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2026)
This study aims to analyze the operational legality and the level of sharia compliance of Kitabisa.com in the development of digital technology has driven the transformation of Islamic philanthropic practices in Indonesia, one of which is through the utilization of online crowdfunding platforms such as Kitabisa.com. the practice of digital Islamic philanthropy in Indonesia. The research employs a normative legal research method, with a content analysis approach used to examine digital content related to Islamic philanthropic practices on the Kitabisa.com platform. The analysis focuses on messages, visuals, narratives, as well as the mechanisms for fund management and distribution presented in digital Islamic philanthropy campaigns. The results indicate that Kitabisa.com has legally operated in accordance with applicable legal norms, particularly those related to the operation of electronic systems and public fundraising activities. From a sharia perspective, the mechanisms for fundraising and fund distribution implemented by Kitabisa.com are generally in line with Islamic philanthropic values, such as trustworthiness, transparency, justice, and public benefit. Nevertheless, strengthening sharia supervision remains necessary to ensure that the management of religious funds is more optimal and fully compliant with sharia principles. Therefore, Kitabisa.com has the potential to become an effective and sustainable instrument of digital Islamic philanthropy in Indonesia.